Vt cecinit poeta : The presence of Virgil in Rodrigo de Castro's De uniuersa mulierum medicina - Silva, Gabriel A. F. (2021)
De uniuersa mulierum medicina, by the Portuguese physician Rodrigo de Castro, is a complex gynaecological treatise that comprises sources concerning various medical aspects, both ancient and contemporary to the author, and also non-technical sources, namely poets from classical antiquity. This being the first article on the presence of Virgil in Castro, the main goal is to see where Virgil’s Georgics 4 and Aeneid 6 are used in the De uniuersa mulierum medicina and explore how passages from the Virgilian oeuvre were used by the Portuguese physician.